Systematic phonics instruction belongs in evidence-based reading programs: A response to Bowers. (16th December 2020) - Buckingham, Jennifer
Abstract: This article is a rejoinder to J.S. Bowers (2020), 'Reconsidering the evidence that systematic phonics is more effective than alternative methods of reading instruction', Educational Psychology Review (https://doi.org/10.1007/s10648-019-09515-y ). There is strong agreement among reading scientists that learning the phonological connections between speech and print is an essential element of early reading acquisition. Meta-analyses of reading research have consistently found that methods of reading instruction that include systematic phonics instruction are more effective than methods that do not. This article critiques a recent article by Jeffery S. Bowers that attempts to challenge the robustness of the research on systematic phonics instruction. On this basis, Bowers proposes that teachers and researchers consider using alternative methods. This article finds that even with a revisionist and conservative analysis of the research literature, the strongest available evidence shows systematic phonics instruction to be more effective than any existing alternative. While it is fair to argue that researchers should investigate new practices, it is irresponsible to suggest that classroom teachers use anything other than methods based on the best evidence to date, and that evidence favours systematic phonics.